Comparison of Extracorporeal Shockwave and High-Intensity Laser in Treating Chronic Plantar Fasciitis - Saba Riaz, Aroona Sattar, Pakeeza Seemal, Rabia Majeed, Aqsa Naveed, Nouman Abid, Salman Bashir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Plantar fasciitis (PF), an inflammation of the plantar fascia. This study compared the effects of the extracorporeal shockwave and high-intensity laser in reducing pain and enhancing function in chronic plantar fasciitis patients, who have failed to achieve results by the conservative treatment. Aim: To explore the best non-invasive treatment option for chronic PF within the scope of physical therapy. Method: After registry of trial the data collection was started.A total of45 chronic PF patientswere divided, randomly into three groups. Group 1 received BTL-6000 Shockwave therapy (ESWT) , group 2 received Diowave 60W Class IV hot Laser (HILT) and group 3 (the control group) was not given any electrotherapy treatment. All groups were given some exercises for the home plan. The groups were assessed with the Visual Analogue scale (VAS) and foot functional index (FFI) at baseline, post-treatment, and follow-up of 2 months. Result: The mean age of participants was 39.66±10.05,38.06 ±12.64 and 37.40±13.18 for ESWT, HILT group and control groups respectively. There was significant difference in VAS and FFI score p=<0.001 across the time. Pre-treatment and post-treatment scores were significantly different but post treatment and follow-up scores were not significantly different for both VAS and FFI score (p=1.00). Practical implication: This study will help us to find out chronic Plantar fasciitis treatment within physical therapy and electrotherapy domain. As both these modalities are non-invasive, cost effective and proved as effective treatment for reduction of pain and improvement of pain in chronic plantar fasciitis patients. Conclusion: Extracorporeal shockwave have been promising treatment for chronic plantar fasciitis but High intensity LASER therapy effectiveness was not explored a lot in previous literature. The study concluded that both ESWT and HILT are effective in reducing pain and improving function on VAS and FFI, though the ESWT group was found better than both groups in FFI score and VAS across time on the basis of the mean differences across time. Keywords: Exercise, Extra-corporeal shockwave therapy, heel pain, High-intensity Laser therapy, Plantar fasciitis